STRATEGI INTERVENSI UNTUK MENEKAN KASUS KEKERASAN SEKSUAL: ISU DAN TREN - Nona Carolina; Wisnu Aji Saputra; Hilda Hidayatun Nafi’ah; Yulia Gesti Merkuri; Caraka Putra Bakti (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2022)
The case of sexual violence in Indonesia has now become a public discussion. The victims involved range from teenagers to even minors, girls and boys. Factors that influence a person to commit sexual violence include addiction to pornographic videos, lack of parental supervision, family conditions that are not harmonious (broken home). The method used in this study uses a qualitative approach, namely by using a literature review. The results of this study indicate that cases of sexual violence in Indonesia have increased significantly every year. This is evidenced by data findings in 2020, which show that sexual violence against women during the COVID-19 pandemic increased by 21% (1,731 cases). Meanwhile, according to data from the Ministry of Women's Empowerment and Child Protection (PPPA), there were 5,488 cases of sexual violence in Indonesia. Based on the Report of the Quantitative Study of the Gender Equality Barometer launched by the Indonesia Judicial Research Society (IJRS) and INFD in 2020, it is stated that there are approximately 33% of men in Indonesia experience sexual harassment. The conclusion of this study resulted in the finding that sexual violence did not look at age and gender. So, guidance and counseling are necessary as a preventive effort to increase cases of sexual violence in Indonesia.